2017
DOI: 10.1038/mi.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prebiotics on microbial dysbiosis, butyrate production and immunity in HIV-infected subjects

Abstract: Altered interactions between the gut mucosa and bacteria during HIV infection seem to contribute to chronic immune dysfunction. A deeper understanding of how nutritional interventions could ameliorate gut dysbiosis is needed. Forty-four subjects, including 12 HIV viremic untreated (VU) patients, 23 antiretroviral therapy-treated (ART) virally suppressed patients (15 immunological responders and 8 non-responders) and 9 HIV controls (HIV), were blindly randomized to receive either prebiotics (scGOS/lcFOS/glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 78 publications
5
105
2
Order By: Relevance
“…The source of butyrate in the blood of the longitudinal cohort is currently unclear. Since gut and vaginal microbiomes also have HIV associated dysbiosis with epithelial dysfunction (Borgdorff et al, 2016; Serrano-Villar et al, 2016) non-pulmonary sources may contribute to the HIV associated SCFA elevation in the blood. Additionally, the BAL studies are cross sectional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of butyrate in the blood of the longitudinal cohort is currently unclear. Since gut and vaginal microbiomes also have HIV associated dysbiosis with epithelial dysfunction (Borgdorff et al, 2016; Serrano-Villar et al, 2016) non-pulmonary sources may contribute to the HIV associated SCFA elevation in the blood. Additionally, the BAL studies are cross sectional.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of the contribution of bacterial SCFA production to local immune suppression will require placebo-controlled randomized clinical trials using SCFA as a measurable outcome. If anaerobically-produced SCFA are immune-compromising, then antibiotic or prebiotic treatments that reduce SCFA (Serrano-Villar et al, 2016) might improve immune response.…”
Section: Discussionmentioning
confidence: 99%
“…). A recent interventional study administering prebiotics to HIV patients found that short dietary supplementation attenuated gut dysbiosis and systemic inflammation . However, longitudinal studies in humans and experimental work in mice are needed to delineate a causal relationship between HIV‐induced Prevotella ‐rich dysbiosis, inflammation and adverse disease outcomes.…”
Section: Gut Dysbiosis Triggered By Hivmentioning
confidence: 99%
“…High-throughput sequencing analysis of the 16S gene in the microbial genome revealed that there were significant increases in the quantities of microbes in the families g_Helicobacter, f_Desulfovibrionaceae, Mucispirillum_schaedleri_ASF457, and g_Blautia in the faeces of mice treated with ranitidine and finasteride, whereas the relative abundances of microbes in the families Enterobacter_sp_.IPC1-8 and g_Bacteroides were significantly reduced. The prevalence of corresponding metabolic pathways, such as nucleotide and cofactor and vitamin metabolismwere significantly increased, whereas those of metabolic signalling pathways related to glycan biosynthesis and metabolism and cardiovascular diseases were significantly reduced.It is known that Blautia can proliferate under the stimulation of prebiotics and is a typical beneficial bacteria [27,28]. Serrano-Villar S et al found that Blautia was significantly increased in the gut microbiota when normal individuals consumed probiotics [27].…”
Section: Discussionmentioning
confidence: 99%